Consumers' preference for eco-friendly packaged products: pride vs guilt appeal - Shimul, Anwar Sadat; Cheah, Isaac (EMERALD GROUP PUBLISHING LTD, 2023)
Purpose: This paper aims to examine the influence of eco-friendly packaging on consumers' responses. A research framework is examined to identify significant antecedents of eco-friendly packaging behaviour, namely environmental responsibility, knowledge, attitudes, and message framing, to determine their relative importance. Design/methodology/approach: A set of hypotheses is tested across two studies. Findings: Study 1 (n = 160) shows that attitude is an important mediator between consumers' environmental responsibility and environmental knowledge and intentions when adopting eco-friendly packaging. Furthermore, study 2 (n = 132) finds that where eco-friendly packaging is concerned, the advertised message has to be framed with a particular emotional appeal congruent to a specific psychographic trait to stimulate pro-environmental behavioural intention. Practical implications: Based on the findings of this research, advertisers and environmental practitioners can utilise the correct type of message appeals to implement pro-environmental campaigns and programs for appropriate consumer segments effectively. Originality/value: Aligning with the United Nations Sustainable Development Goals (SDGs), in particular, SDGs 12 on ensuring “responsible consumption and production”, the research findings have highlighted the importance of individual's environmental knowledge (eco-literacy) and responsibility as they act as precursors toward sustainable and responsible consumption.